Molecular aspects of the ribosomal peptidyl transferase. (November 2002) - Dorner, S.; Polacek, N.; Schulmeister, U.; Panuschka, C.; Barta, A.
Abstract : The proteins in a living cell are synthesized on a large bipartite ribonucleoprotein complex termed the ribosome. The peptidyl transferase, which polymerizes amino acids to yield peptides, is localized on the large subunit. Biochemical investigations over the past 35 years have led to the hypothesis that rRNA has a major role in all ribosomal functions. The recent high resolution X-ray structures of the ribosomal subunits clearly demonstrated that peptidyl transfer is an RNA-mediated process. As all ribosomal activities are dependent on bivalent metal ions, as is the case for most ribozymes, we investigated metal-ion-binding sites in rRNA by metal-ion-cleavage reactions. Some cleavage sites are near active sites and are evolutionarily highly conserved. The structure of the active site is flexible and undergoes changes during translocation and activation of the ribosome. Using modified P-site substrates, we showed that the 2′-OH group of the terminal adenosine is important for peptidyl transfer. These substrates were also used to investigate the metal ion dependency of the peptidyl transferase reaction.